(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The research aims to reveal the effectiveness of computer simulations for developing conceptual comprehension in science among second-year intermediate school students in Al-Kharj Governorate, using the quasi-experimental approach. To answer the research questions, the researcher built the research tool, which is a conceptual comprehension test that measures the level of explanation, interpretation, and application. The research population consisted of (3,114) female students in the second intermediate grade in Al-Kharj Governorate, while the research sample was chosen by a simple random method and consisted of (49) female students from the second intermediate grade in the eighteenth intermediate school for girls in Al-Kharj Governorate, which was chosen by a simple random method. The sample was divided into two equal groups: the experimental group, consisting of (28) female students, and the control group, consisting of (21) female students. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) program, and the results of the research confirmed the effectiveness of computer simulations for developing conceptual understanding in science among female second-year intermediate students in Al-Kharj Governorate. The researcher recommends producing educational simulation programs that support the Arabic language for various educational levels in science.